Validation of analytical methodology for determination of Personal Care Products in environmental matrix by GC-MSMS - Filippe, Tais Cristina; de Almeida Brehm Goulart, Franciane; Mizukawa, Alinne; Rodrigues de Azevedo, Júlio César (Eclética Química, 2018)
The presence of personal care products in the environment is recent and relatively few researches work with the quantification of this class of emerging contaminants in Brazil. However, a wide variety of these products is continuously released into the aquatic environment. The growing interest in these substances occurs mainly because they exhibit biological activity in very low concentrations, which gives great environmental relevance. The difficulty of detecting and quantifying such contaminants in the environment encourages the development and validation of appropriate analytical methods for this purpose. Therefore, the present study aims to validate a methodology and verify its efficiency in the determination of six personal care products, among them parabens and triclosan. The samples were submitted to the solid phase extraction process and were later analyzed by gas chromatography coupled with mass spectrometry for the determination of personal care products. The validation of the methodology used was based on the standards established by the National Health Surveillance Agency. The extraction and quantification method were efficient for the determination of these analytes in water samples.